The microvascular endothelial glycocalyx: An additional piece of the puzzle in veterinary medicine. (July 2022) - Lawrence-Mills, Sara J.; Hughes, David; Hezzell, Melanie J.; Butler, Matthew; Neal, Chris; Foster, Rebecca R.; Welsh, Gavin I.; Finch, Natalie
Abstract: The endothelial glycocalyx (eGlx) is a critically important structure lining the luminal surface of endothelial cells. There is increasing evidence, in human patients and animal models, for its crucial role in the maintenance of health. Moreover, its damage is associated with the pathogenesis of multiple disease states. This review provides readers with an overview of the eGlx; summarising its structure, essential functions, and evidence for its role in disease. We highlight the lack of studies regarding the eGlx in cats and dogs, particularly in naturally occurring diseases. Importantly, we discuss techniques to aid its study, which can be applied to veterinary species. Finally, we present targeted therapies aimed at preserving, and in some cases, restoring damaged eGlx. Highlights: The endothelial glycocalyx is critical in maintaining vascular health. Glycocalyx visualisation and measurement is technically challenging. There is growing evidence for the role of glycocalyx breakdown in human disease. Research is needed to understand glycocalyx degradation in disease in dogs and cats.